Insensitivity of auditory mismatch negativity to classical fear conditioning and extinction in healthy humans. Issue 7 (1st May 2019) - Kurayama, Taichi; Matsuzawa, Daisuke; Hirano, Yoshiyuki; Shimizu, Eiji
Abstract : The relationship between auditory mismatch negativity (MMN) and the neural cognitive processes of fear has been suggested in both healthy participants and patients with fear-related mental disorders such as post-traumatic stress disorder and panic disorder. The present study sought to confirm whether the MMN is affected by classical fear conditioning in healthy participants. MMN amplitude, N1 amplitude, and skin conductance level (SCL) in 20 healthy volunteers during a fear-conditioning paradigm consisting of three phases (habituation, fear acquisition, and fear extinction) were recorded. Red and blue light signals were presented as the conditioned stimuli CS+ (threat cue) and CS− (safety cue), respectively. In addition, an aversive electrical stimulus was delivered as the unconditioned stimulus with CS+ in the fear-acquisition phase. No MMN amplitude changes were observed between the CS types during the three phases. In the acquisition phase, the mean SCL during CS+ was significantly higher than that during CS−. The MMN amplitude and deviant N1 amplitude in the extinction phase were significantly lower than those in the other phases regardless of the CS type. Despite the clear alteration of SCL between CS types in the acquisition phase, no significant differences in MMN were observed. Decreased MMN and deviant N1 in the fear-extinction phase were considered to be mainly due to decreased arousal or attention level. Results indicate that the auditory MMN amplitude was not affected by the cognitive process of fear recognized by other sense modalities.